The Enf-of-life Process in Palliative Cancer Patients in a Hospital and at Home Satting: Qualitative Study - Araújo, Vânia (2018)
Background: palliative care emerges in the sense of providing a better quality of life for terminal patients. This care can be provided in different contexts, namely, hospital stay, outpatient clinic and at home. Objective: the present study aims to understand how the end-of-life process in palliative cancer patients in hospital care (DOPH) and at home (DOPD) in the sense of accessing the depth of their experiences. Methodology: qualitative study with 20 palliative cancer patients, 10 DOPH and 10 DOPD, aged between 50 and 89 years. To collect the data, we used the semi-structured interview and for the respective analysis to the categorizing system of the content analysis based in Bardin (2008). Results: ln both contexts patients report needing information and clarification, also showing hope for cure and for treatments to stop the disease. Patients report emotional suffering in the face of their finitude, through feelings of sadness and even loss of the meaning of life. Conclusion: no specificities were found in communication, emotional experience and hope, through the context of offering palliative, hospital or home care. The specificities can be understood beyond the context according to the personal, cultural and environmental characteristics of the patients.